Transforming Local History Learning Through Wordwall Media in The Digital Era 4.0 - Sagala, Devita Sari; Sudrajat, Ajat (Universitas Pendidikan Mandalika, 2025)
This study aims to explore the use of Wordwall in transforming local history learning, particularly the topic of Muara Takus Tempel into a more interactive and contextual experience. Employing a qualitative approach with a case study design, the research subjects at SMA Negeri 3 Bukit Batu, Bengkalis, Riau. Data were collected through classroom observation, having conversations with open-ended interviews, and documentation, and were analyzed using source triangulation. The findings indicate that the use of Wordwall enhanced student understanding, fostered a more interactive classroom atmosphere, and increased learners’ interest in history. These results suggest that digital tools like Wordwall can serve as effective strategies for making local history learning more engaging, relevant, and aligned with the demands of the digital era.